The utilization of digital mathematics comics as an effort to enhance literacy and numeracy and to instill character in Students - Khasanah, Binti Anisaul; Hartono, Susilo; Nurdin, Astoni (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
In accordance with the main problem, namely a decline in assessment results on literacy, numeracy and character indicators of SD Muhammadiyah Waringinsari from 2022 to 2023. So it is necessary to carry out PKM activities with the aim of improving the ability of teachers in partner schools in creating digital media in the form of digital comics in an effort to improve literacy and numeracy as well as in an effort to instill character through the storyline in digital comics. SD Muhammadiyah Waringinsari already has technological support from both the government and the Muhammadiyah Association. Teachers also have personal technological facilities such as laptops and cellphones that are used in digital learning. Some of the points produced and achieved in this PKM include; teachers can produce digital comics well, and the level of understanding of partners at the beginning and end of the activity regarding the material presented during the workshop was measured using a pretest and posttest, the results increased. The next activity is in the form of mentoring and scaffolding in the creation of digital mathematics comic media for teachers of grades 3, 4, 5, and 6. Through this activity, it is hoped that teachers will be able to design digital mathematics comic media for use in learning activities so that students' literacy and numeracy increase and can instill character through the storyline in the digital comic.